Fish Identification in The Bunter Lake, Pangkalan Baru Village Siak Hulu District, Kampar Regency, Riau Province - Nashuha Faridhita; Windarti Windarti; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Bunter lake is an oxbow lake that receive water from the Kampar River during the rainy season. This lake is inhabited by many fish species, however, the information about the type of fish in that area is limited. To understand the types of fish present in the Bunter lake, a study has been conducted in March to April 2019. Fish sampling were conducted every day for two weeks or there is no new species found. The fishes were captured using lures, gill nets and bamboo traps. Fish samples were then identified. Results shown that the caught fish consists of 3 orders, 16 families, 27 genera and 30 species. Among 30 species captured, 2 species were categorized as ornamental fish, 12 species were edible fishes and 16 species were ornamental-edible fishes. The water quality of the lake were as follows: temperature of 29oC-30oC, brightness of 40-65 cm, pH of 6, dissolved oxygen of 3.8-4.4 mg/L and carbondioxide 5.99-7.99 mg/L. Keywords: Oxbowlake, Rainy season, Ornamental fish, Edible fishes, Ornamental-edible fishes